Comprehensive Bioinformatics Analysis to Reveal Key RNA Targets and Hub Competitive Endogenous RNA Network of Keratoconus - Ouyang, Shuai; Ma, Jingyu; Sun, Qihang; Li, Jinyan; Chen, Yijia; Luo, Lixia (Frontiers in Genetics, 2022)
Keratoconus (KC) is the most common corneal ectatic disease. We mainly performed bioinformatics approaches to reveal core RNA targets, hub competitive endogenous RNA (ceRNA) network and explored the potential regulatory mechanisms of ceRNA in KC. The high‑throughput sequencing datasets GSE77938 and GSE151631 were downloaded from the Gene Expression Omnibus (GEO) database. We identified the differential expression of mRNAs and lncRNAs using DESeq2 package. Functional enrichment analyses and Keratoconus (KC) is the most common corneal ectatic disease with its pathological mechanisms unclear. We mainly performed bioinformatics approaches to reveal core RNA targets, hub competitive endogenous RNA (ceRNA) network and explored the potential regulatory mechanisms of ceRNA in KC. The high‑throughput sequencing datasets GSE77938 and GSE151631 were downloaded from the Gene Expression Omnibus (GEO) database. The differential expression of mRNAs and lncRNAs were identified using DESeq2 package. Functional enrichment analyses and protein-protein interaction (PPI) were executed. Then, the hub genes were filtered and molecular docking analysis was performed. Moreover, we predicted miRNAs through website database and validated them using quantitative PCR (qPCR). Eventually, lncRNA-miRNA-mRNA regulatory network was constructed by Cytoscape. We revealed that 428 intersected differentially expressed mRNA (DEGs) and 68 intersected differentially expressed lncRNA (DELs) were shared between the two datasets. Functional enrichment results novelty showed that ubiquitin−dependent protein catabolic process was upregulated in KC. The pathway enrichment showed DEGs were mainly involved in NF-kB signaling and neurodegenerative diseases. In addition, we uncovered top 20 hub genes in which FBXW11, FBXO9, RCHY1 and CD36 were validated by qPCR. Particularly, a small molecule drug, Triptolide was predicted by molecular docking as candidate drug for treating KC. Moreover, we innovatively predicted and validated 4 core miRNAs (miR-4257, miR-4494, miR-4263 and miR-4298) and constructed ceRNA network which contained 165 mRNA, 8 lncRNAs and 4 core miRNAs. Finally, we proposed a potential regulatory mechanism of KC. Overall, we uncovered a hub ceRNA network that might underlie a critical post-translational regulatory mechanism in KC, in which miR-4257, miR-4494, miR-4263 and miR-4298 could be valuable biomarkers and provided core RNAs therapeutic targets for KC.